In vitro evaluation of pectin-HPMC compression coated 5-aminosalicylic acid tablets for colonic delivery - UĞURLU, TİMUÇİN (My University, 2002)
In this study, we report pectin-HPMC compression coated core tablets of 5-aminosalicylic acid (5-ASA) for colonic delivery. Each 100 mg core tablet contained 5-ASA and was compression coated at 20 kN or 30 kN using 100% pectin, 80% pectin-20% HPMC, or 60% pectin-40% HPMC, at two different coat weights as 400 or 500 mg. Drug dissolution/system erosion/degradation studies were carried out in pH 1.2 and 6.8 buffers using a pectinolytic enzyme. The system was designed based on the gastrointestinal transit time concept, under the assumption of colon arrival times of 6 h. It was found that pectin alone was not sufficient to protect the core tablets and HPMC addition was required to control the solubility of pectin. The optimum HPMC concentration was 20% and such system would protect the cores up to 6 h that corresponded to 25-35% erosion and after that under the influence of pectinase the system would degrade faster and delivering 5-ASA to the colon. The pectin-HPMC envelope was found to be a promising drug delivery system for those drugs to be delivered to the colon.
Keywords: Drug Evaluation, Preclinical; Colon; Compressive Strength; Anti-Inflammatory Agents, Non-Steroidal; Tablets, Enteric-Coated; Solubility; Methylcellulose; Pectins; Lactose; Drug Delivery Systems; Mesalamine; Oxazines; Antidiarrheals